Aluminum alloy with silicon, magnesium, copper and zinc

A tailored aluminum alloy composition with controlled Si, Mg, Zn, and Cu content addresses the challenge of achieving high strength and formability, enhancing mechanical properties and corrosion resistance for automotive applications.

JP7599438B2Active Publication Date: 2024-12-13ARCONIC TECHNOLOGIES LLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021569878
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-06
Filing Date
2020-05-20
Publication Date
2024-12-13
Estimated Expiration
2040-05-20

AI Technical Summary

Technical Problem

Existing 6xxx series aluminum alloys face challenges in achieving a combination of excellent formability before heat treatment and high strength after heat treatment without degrading other properties.

Method used

A new aluminum alloy composition with specific ranges of Si, Mg, Zn, Cu, and other elements, totaling 4.25% or less, along with controlled ratios and amounts of additional components, enhances properties such as strength, formability, and corrosion resistance.

Benefits of technology

The alloy achieves improved mechanical properties, including low strength after natural aging, high strength after paint baking, and enhanced ductility, while maintaining corrosion resistance, suitable for automotive applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599438000001
    Figure 0007599438000001
  • Figure 0007599438000002
    Figure 0007599438000002
  • Figure 0007599438000003
    Figure 0007599438000003
Patent Text Reader

Abstract

A new aluminum alloy is disclosed. The new aluminum alloy may contain 0.70-1.4 wt.% Si, 0.70-1.3 wt.% Mg, where (wt.% Mg) / (wt.% Si) is 1.40 or less, 0.70-3.0 wt.% Zn, 0.55-1.3 wt.% Cu, where the total of Si + Mg + Zn + Cu is 4.25 wt.% or less, 0.01-0.30 wt.% Fe, up to 0.70 wt.% Mn, up to 0.15 wt.% Cr, up to 0.20 wt.% Zr, up to 0.20 wt.% V, and up to 0.25 wt.% Ti, with the balance being aluminum, optional unavoidable elements, and impurities. The new aluminum alloy may realize an improved combination of properties, such as an improved combination of strength, formability, and / or corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] The 6xxx series aluminum alloy is an aluminum alloy having silicon and magnesium that forms magnesium silicide (Mg2Si) precipitation. The 6061 alloy has been used for various applications for decades. However, it has not been clear how to improve one or more properties of the aluminum alloy without degrading other properties. In automotive applications, sheets that have excellent formability before heat treatment but high strength after heat treatment are useful.

Summary of the Invention

[0002] Generally, this patent application relates to a novel aluminum alloy and a method for manufacturing the same. The novel aluminum alloy generally contains 0.70 to 1.4 wt% Si, 0.70 to 1.3 wt% Mg, where (wt% of Mg) / (wt% of Si) is 1.40 or less, 0.70 to 3.0 wt% Zn, 0.55 to 1.3 wt% Cu, where the total amount of Si + Mg + Zn + Cu is 4.25 wt% or less, 0.01 to 0.30 wt% Fe, up to 0.70 wt% Mn, up to 0.15 wt% Cr, up to 0.20 wt% Zr, up to 0.20 wt% V, up to 0.25 wt% Ti, and the balance is aluminum, optional inevitable elements, and impurities. The novel aluminum alloy can achieve an improvement in a combination of properties, such as an improvement in a combination of two or more of, for example, strength after natural aging treatment, paint baking strength, T6 strength, formability, ductility, and corrosion resistance. The novel aluminum alloy can be used for various applications, such as automotive applications (e.g., as sheet products).

[0003] <i.Composition> As indicated above, the new aluminum alloy generally comprises (and in some examples consists essentially of, or consists of) 0.70-1.4 wt.% Si, 0.70-1.3 wt.% Mg, where (wt.% Mg) / (wt.% Si) is 1.40 or less, 0.70-3.0 wt.% Zn, and 0.55-1.3 wt.% Cu, where the total of Si+Mg+Zn+Cu is 4.25 wt.% or less, and 0.01-0.30 wt.% Fe, up to 0.70 wt.% Mn, up to 0.15 wt.% Cr, up to 0.20 wt.% Zr, up to 0.20 wt.% V, and up to 0.25 wt.% Ti, the balance being aluminum, optional unavoidable elements, and impurities. The use of these particular amounts of elements can result in uniquely useful products for use in, for example, automotive applications where good formability is required before heat treatment and high strength is also required after heat treatment.

[0004] As noted above, the new aluminum alloy generally includes 0.70-1.4 wt.% Si. Silicon can promote strength. As shown in the examples below, use of silicon beyond this range can be detrimental. In one embodiment, the new aluminum alloy includes at least 0.75 wt.% Si. In another embodiment, the new aluminum alloy includes at least 0.80 wt.% Si. In yet another embodiment, the new aluminum alloy includes at least 0.85 wt.% Si. In one embodiment, the new aluminum alloy includes no more than 1.35 wt.% Si. In another embodiment, the new aluminum alloy includes no more than 1.30 wt.% Si. In yet another embodiment, the new aluminum alloy includes no more than 1.25 wt.% Si. In another embodiment, the new aluminum alloy includes no more than 1.20 wt.% Si. In yet another embodiment, the new aluminum alloy includes no more than 1.15 wt.% Si. In another embodiment, the new aluminum alloy includes no more than 1.10 wt.% Si. In yet another embodiment, the new aluminum alloy includes no more than 1.05 wt.% Si.

[0005] As noted above, the novel aluminum alloy generally includes 0.70-1.3 wt.% Mg. Magnesium can promote strength. As shown in the examples below, use of magnesium beyond this range can be detrimental. In one embodiment, the novel aluminum alloy includes at least 0.75 wt.% Mg. In another embodiment, the novel aluminum alloy includes at least 0.80 wt.% Mg. In one embodiment, the novel aluminum alloy includes no more than 1.25 wt.% Mg. In another embodiment, the novel aluminum alloy includes no more than 1.20 wt.% Mg. In yet another embodiment, the novel aluminum alloy includes no more than 1.15 wt.% Mg. In another embodiment, the novel aluminum alloy includes no more than 1.10 wt.% Mg. In yet another embodiment, the novel aluminum alloy includes no more than 1.05 wt.% Mg.

[0006] As noted above, the weight ratio of Mg:Si is generally 1.4:1 or less. An appropriate Mg:Si ratio can promote corrosion resistance at applicable strength levels. As shown in the examples below, use of Mg:Si ratios outside this range can be detrimental. In one embodiment, the weight ratio of Mg:Si is 1.3:1 or less. In another embodiment, the weight ratio of Mg:Si is 1.2:1 or less. In one embodiment, the weight ratio of Mg:Si is at least 0.7:1. In another embodiment, the weight ratio of Mg:Si is at least 0.8:1. In yet another embodiment, the weight ratio of Mg:Si is at least 0.9:1.

[0007] As noted above, the new aluminum alloy generally includes 0.70-3.0 wt.% Zn. Zinc can promote strength and proper natural aging response. As shown in the examples below, use of zinc beyond this range can be detrimental. In one embodiment, the new aluminum alloy includes at least 0.75 wt.% Zn. In another embodiment, the new aluminum alloy includes at least 0.85 wt.% Zn. In yet another embodiment, the new aluminum alloy includes at least 0.95 wt.% Zn. In another embodiment, the new aluminum alloy includes at least 1.0 wt.% Zn. In yet another embodiment, the new aluminum alloy includes at least 1.05 wt.% Zn. In one embodiment, the new aluminum alloy includes up to 2.8 wt.% Zn. In another embodiment, the new aluminum alloy includes up to 2.6 wt.% Zn. In yet another embodiment, the new aluminum alloy includes up to 2.4 wt.% Zn. In another embodiment, the new aluminum alloy includes up to 2.2 wt.% Zn. In yet another embodiment, the new aluminum alloy includes up to 2.0 wt.% Zn. In another embodiment, the new aluminum alloy includes up to 1.8 wt.% Zn.

[0008] As noted above, the new aluminum alloy generally includes 0.55-1.3 wt.% Cu. Copper can promote strength, corrosion resistance, and natural aging response. As shown in the examples below, use of copper beyond this range can be detrimental. In one embodiment, the new aluminum alloy includes at least 0.60 wt.% Cu. In another embodiment, the new aluminum alloy includes at least 0.65 wt.% Cu. In yet another embodiment, the new aluminum alloy includes at least 0.70 wt.% Cu. In one embodiment, the new aluminum alloy includes no more than 1.25 wt.% Cu. In another embodiment, the new aluminum alloy includes no more than 1.20 wt.% Cu. In yet another embodiment, the new aluminum alloy includes no more than 1.15 wt.% Cu. In another embodiment, the new aluminum alloy includes no more than 1.10 wt.% Cu. In yet another embodiment, the new aluminum alloy includes no more than 1.05 wt.% Cu.

[0009] As noted above, the solutes in the alloy are limited, with the total of Si+Mg+Zn+Cu not exceeding 4.25% by weight. As shown in the examples below, the use of excess solutes can be detrimental, hence the stated limits.

[0010] As indicated above, the new aluminum alloy generally comprises 0.01-0.30 wt.% Fe. Iron can promote proper grain structure and it can be cost-effective to use more than 0.10 wt.% Fe. Use of iron beyond this range may not be cost-effective and / or harmful. It is necessary to limit the amount of iron in the alloy so that large primary particles during the manufacture of the aluminum alloy product are avoided / restricted / limited. In one embodiment, the new aluminum alloy comprises at least 0.05 wt.% Fe. In another embodiment, the new aluminum alloy comprises at least 0.10 wt.% Fe. In yet another embodiment, the new aluminum alloy comprises at least 0.12 wt.% Fe. In one embodiment, the new aluminum alloy comprises 0.25 wt.% or less Fe. In another embodiment, the new aluminum alloy comprises 0.22 wt.% or less Fe. In yet another embodiment, the new aluminum alloy comprises 0.19 wt.% or less Fe. In another embodiment, the new aluminum alloy comprises 0.16 wt.% or less Fe.

[0011] As indicated above, the new aluminum alloy may include up to 0.70 wt.% Mn. Manganese can promote proper grain structure. Use of manganese above this range can be detrimental. It is necessary to limit the amount of manganese in the alloy so that large primary particles are avoided / restricted / limited during the manufacture of aluminum alloy products. In one embodiment, the new aluminum alloy includes at least 0.05 wt.% Mn. In another embodiment, the new aluminum alloy includes at least 0.10 wt.% Mn. In yet another embodiment, the new aluminum alloy includes at least 0.15 wt.% Mn. In one embodiment, the new aluminum alloy includes no more than 0.60 wt.% Mn. In another embodiment, the new aluminum alloy includes no more than 0.50 wt.% Mn. In yet another embodiment, the new aluminum alloy includes no more than 0.45 wt.% Mn. In another embodiment, the new aluminum alloy includes no more than 0.40 wt.% Mn.

[0012] As indicated above, the new aluminum alloy includes 0.15 wt.% or less Cr. Use of more than 0.15 wt.% Cr may be detrimental to the grain structure and may cause problems with the recyclability of the alloy. In one embodiment, the new aluminum alloy includes 0.12 wt.% Cr or less. In another embodiment, the new aluminum alloy includes 0.10 wt.% Cr or less. In yet another embodiment, the new aluminum alloy includes 0.08 wt.% Cr or less. In another embodiment, the new aluminum alloy includes 0.06 wt.% Cr or less. In yet another embodiment, the new aluminum alloy includes 0.04 wt.% Cr or less. In another embodiment, the new aluminum alloy includes 0.03 wt.% Cr or less. In yet another embodiment, the new aluminum alloy includes 0.02 wt.% Cr or less. In another embodiment, the new aluminum alloy includes 0.01 wt.% Cr or less.

[0013] As indicated above, the new aluminum alloy includes 0.20 wt.% Zr or less. Zirconium is less desirable than manganese for grain structure control, but can still be useful. It is necessary to limit the amount of zirconium in the alloy so that large primary particles during the manufacture of the aluminum alloy product are avoided / restricted / limited. In one embodiment, the new aluminum alloy includes 0.15 wt.% Zr or less. In another embodiment, the new aluminum alloy includes 0.10 wt.% Zr or less. In yet another embodiment, the new aluminum alloy includes 0.08 wt.% Zr or less. In another embodiment, the new aluminum alloy includes 0.03 wt.% Zr or less. In yet another embodiment, the new aluminum alloy includes 0.01 wt.% Zr or less. In one embodiment, the new aluminum alloy includes at least 0.01 wt.% Zr (e.g., when Zr is added / used in the alloy for grain structure control). In another embodiment, the new aluminum alloy includes at least 0.05 wt.% Zr. In one embodiment, the novel aluminum alloy includes 0.07 to 0.15 wt. % Zr.

[0014] As indicated above, the new aluminum alloy includes 0.20 wt.% or less V. Vanadium is less desirable than manganese for grain structure control, but can still be useful. It is necessary to limit the amount of vanadium in the alloy so that large primary particles during the manufacture of the aluminum alloy product are avoided / restricted / limited. In one embodiment, the new aluminum alloy includes 0.15 wt.% or less V. In another embodiment, the new aluminum alloy includes 0.10 wt.% or less V. In yet another embodiment, the new aluminum alloy includes 0.08 wt.% or less V. In another embodiment, the new aluminum alloy includes 0.03 wt.% or less V. In yet another embodiment, the new aluminum alloy includes 0.01 wt.% or less V. In one embodiment, the new aluminum alloy includes at least 0.01 wt.% V (e.g., when V is added / used in the alloy for grain structure control). In another embodiment, the new aluminum alloy includes at least 0.05 wt.% V. In one embodiment, the new aluminum alloy includes 0.07-0.15 wt.% V.

[0015] As indicated above, the new aluminum alloy includes 0.25 wt.% Ti or less. Titanium may be used during casting for grain refinement. Higher concentrations of titanium may also promote corrosion resistance. It is necessary to limit the amount of titanium in the alloy so that large primary particles during the production of the alloy product are avoided / restricted / limited. In one embodiment, the new aluminum alloy includes at least 0.005 wt.% Ti. In another embodiment, the new aluminum alloy includes at least 0.01 wt.% Ti. In yet another embodiment, the new aluminum alloy includes at least 0.02 wt.% Ti. In yet another embodiment, the new aluminum alloy includes at least 0.05 wt.% Ti. In one embodiment, the new new aluminum alloy includes 0.20 wt.% Ti or less. In another embodiment, the new new aluminum alloy includes 0.15 wt.% Ti or less. In another embodiment, the new new aluminum alloy includes 0.12 wt.% Ti or less. In yet another embodiment, the new new aluminum alloy includes 0.10 wt.% Ti or less. In another embodiment, the new new aluminum alloy includes 0.08 wt.% Ti or less. In yet another embodiment, the new novel aluminum alloy comprises 0.05 wt.% Ti or less. In another embodiment, the new novel aluminum alloy comprises 0.03 wt.% Ti or less. In one embodiment, the new novel aluminum alloy comprises 0.005-0.10 wt.% Ti. In another embodiment, the new aluminum alloy comprises 0.01-0.05 wt.% Ti. In yet another embodiment, the new aluminum alloy comprises 0.01-0.03 wt.% Ti. Titanium may be in elemental or compound form (e.g., TiB2 or TiC).

[0016] As indicated above, the balance of the aluminum alloy is generally aluminum, optional unavoidable elements, and impurities. As used herein, "unavoidable elements" refers to elements or materials, other than those listed above, that can be optionally added to the alloy to aid in the production of the alloy. Examples of unavoidable elements include casting aids, such as grain refiners and deoxidizers. Optional unavoidable elements can be included in the alloy in a cumulative amount of up to 1.0 wt.%. As one non-limiting example, one or more unavoidable elements can be added to the alloy during casting to reduce or limit (and in some cases eliminate) cracking of the ingot, for example, due to oxide folds, pits, and oxide patches. These types of unavoidable elements are generally referred to herein as deoxidizers. Some examples of deoxidizers include Ca, Sr, and Be. When calcium (Ca) is included in the alloy, it is generally present in an amount of up to about 0.05 wt.%, or up to about 0.03 wt.%. In some embodiments, Ca is included in the alloy in an amount of 0.001-0.03% or about 0.05% by weight, such as about 0.001-0.008% by weight (or 10-80 ppm). Strontium (Sr) can be included in the alloy (in whole or in part) as a substitute for Ca, i.e., in the alloy in the same or similar amount as Ca. Traditionally, the addition of beryllium (Be) has helped to reduce the tendency of ingots to crack, but for environmental, health, and safety reasons, some embodiments of the alloy are substantially free of Be. When Be is included in the alloy, it is generally present in an amount up to about 20 ppm. The unavoidable elements may be present in minor or significant amounts, and may themselves add desirable or other properties without departing from the alloys described herein, so long as the alloy retains the desirable properties described herein. However, it should be understood that the scope of the present disclosure should not / cannot be circumvented by merely adding elements in amounts that would not otherwise affect the desired achieved property combinations herein.

[0017] The novel aluminum alloy may contain a small amount of impurities. In one embodiment, the novel aluminum alloy contains a total of 0.15 wt% or less of impurities, and therein the novel aluminum alloy contains each impurity at 0.05 wt% or less. In another embodiment, the novel aluminum alloy contains a total of 0.10 wt% or less of impurities, and therein the novel aluminum alloy contains each impurity at 0.03 wt% or less.

[0018] <ii. Processing> The novel aluminum alloy can be useful in various product forms, including, for example, ingots or ingot pieces, wrought product forms (sheets, forgings, and extrusions), shaped castings, additive manufacturing products, and powder metallurgy products. For example, the novel aluminum alloy can be processed into various wrought forms, such as rolled forms (sheets, plates), extrusions, or forgings, in various tempers. In this regard, the novel aluminum alloy can be cast (e.g., direct chill casting or continuous casting) and then processed (hot worked and / or cold worked) into a suitable product form (sheet, plate, extrusion, or forging). After processing, the novel aluminum alloy can be processed into one of temper T, temper W, or temper F according to ANSI H35.1 (2009). In one embodiment, the novel aluminum alloy is processed (heat treated) into "temper T". In this regard, the novel aluminum alloy can be processed into any of temper T1, T2, T3, T4, T5, T6, T7, T8, T9, or T10 according to ANSI H35.1 (2009). In one embodiment, the product is processed into temper T43 (e.g., according to the following examples). In another embodiment, the product is processed into temper T6 (e.g., according to the following examples). In other embodiments, the novel aluminum alloy is processed into "temper W" (solution heat treated). In another embodiment, no solution heat treatment is applied after processing the aluminum alloy into a suitable product form, and thus, the novel aluminum alloy can be processed into "temper F" (as being secondary processed).

[0019] In one embodiment, the novel aluminum alloy is a sheet product. In one embodiment, the thickness of the sheet product is 1.0 to 4.0 mm. In one embodiment, the sheet product is processed to solution heat treatment T4. In one embodiment, the sheet product is processed to solution heat treatment T43. In one embodiment, the sheet product is processed to solution heat treatment T43 and then painted and baked (e.g., by heating at 180°C for 20 minutes). In one embodiment, the sheet product is processed to solution heat treatment T43, then painted and baked, and then artificially aged to solution heat treatment T6 (e.g., by heating at 180°C for 8 hours). Such sheet products can be useful for automotive applications, as will be described in more detail below.

[0020] <iii. Properties> As shown above, the novel aluminum alloy can achieve an improvement in the combination of properties. In one embodiment, the novel aluminum alloy is a sheet product having a thickness of 1.0 to 4.0 mm, and the sheet product of this aluminum alloy achieves at least one of the following properties: (i) TYS-LT is 155 MPa or less after 7 days of natural aging treatment ("TYS-7NA"), (ii) TYS-LT is 175 MPa or less after 90 days of natural aging treatment ("TYS-90NA"), (iii) (TYS-90NA) minus (TYS-7NA) is 20 MPa or less, (iv) When painted and baked at 180°C for 20 minutes after 30 days of natural aging treatment, TYS-LT is at least 235 MPa, (v) When painted and baked at 180°C for 20 minutes after 90 days of natural aging treatment, TYS-LT is at least 230 MPa, (vi) When artificially aged at 180°C for 8 hours after 30 days of natural aging treatment, TYS-LT is at least 350 MPa. In one embodiment, the aluminium alloy sheet product achieves at least two of the above properties (i)-(vi). In another embodiment, the aluminium alloy sheet product achieves at least three of the above properties (i)-(vi). In yet another embodiment, the aluminium alloy sheet product achieves at least four of the above properties (i)-(vi). In another embodiment, the aluminium alloy sheet product achieves at least five of the above properties (i)-(vi). In yet another embodiment, the aluminium alloy sheet product achieves all of the above properties (i)-(vi).

[0021] As used herein, "TYS-LT" means the transverse tensile yield strength (0.2% offset) of a product as measured in accordance with ASTM E8 and B557.

[0022] As used herein, "TYS-7NA" refers to the transverse tensile yield strength of a product after natural aging for seven days.

[0023] As used herein, "TYS-90NA" refers to the transverse tensile yield strength of a product after natural aging for 90 days.

[0024] As used herein, "paint baking" refers to the application of heat to a product to cure the paint or other polymer thereon. A typical automotive paint bake involves heating to 180°C, then holding at 180°C for 20 minutes (e.g., in an oven), followed by air cooling to ambient temperature.

[0025] As shown above, the new aluminum alloy sheet product may achieve a TYS-LT of 155 MPa or less after seven days of natural aging (i.e., TYS-7NA≦155 MPa). Low strength after natural aging is important to enable subsequent forming of the material (e.g., into automotive seat components). In one embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of 150 MPa or less after seven days of natural aging (i.e., TYS-7NA≦150 MPa). In another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of 145 MPa or less after seven days of natural aging (i.e., TYS-7NA≦145 MPa).

[0026] As shown above, the new aluminum alloy sheet product can achieve a TYS-LT of 175 MPa or less after 90 days of natural aging (i.e., TYS-90NA≦175 MPa). Low strength after natural aging is important to enable subsequent forming of the material (e.g., into automotive seat components). Furthermore, automotive seat products may be in inventory for several months, so the natural aging response / strength needs to be / remain low for extended periods of time. In one embodiment, the new aluminum alloy sheet product can achieve a TYS-LT of 170 MPa or less after 90 days of natural aging (i.e., TYS-90NA≦170 MPa). In another embodiment, the new aluminum alloy sheet product can achieve a TYS-LT of 165 MPa or less after 90 days of natural aging (i.e., TYS-90NA≦165 MPa). In yet another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of 160 MPa or less after 90 days of natural aging (i.e., TYS-90NA≦160 MPa). In another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of 155 MPa or less after 90 days of natural aging (i.e., TYS-90NA≦155 MPa).

[0027] As indicated above, the natural aging response should be low. In one embodiment, the new aluminum alloy sheet product may achieve (TYS-90NA) minus (TYS-7NA) equal to or less than 20 MPa. That is, the strength of the sheet product increases by 20 MPa or less from 7 days to 90 days of natural aging. In another embodiment, the new aluminum alloy sheet product may achieve (TYS-90NA) minus (TYS-7NA) equal to or less than 18 MPa. In yet another embodiment, the new aluminum alloy sheet product may achieve (TYS-90NA) minus (TYS-7NA) equal to or less than 15 MPa. In another embodiment, the new aluminum alloy sheet product may achieve (TYS-90NA) minus (TYS-7NA) equal to or less than 12 MPa. In yet another embodiment, the new aluminum alloy sheet product may achieve (TYS-90NA) minus (TYS-7NA) equal to or less than 10 MPa. In another embodiment, the new aluminum alloy sheet product may realize that (TYS-90NA) minus (TYS-7NA) is equal to or less than 8 MPa.

[0028] As shown above, the new aluminum alloy sheet product may achieve a TYS-LT of at least 235 MPa after natural aging for 30 days and then paint baking at 180°C for 20 minutes. (The phrase "after natural aging for 30 days and then paint baking at 180°C for 20 minutes" is abbreviated herein to "30 day NA+ paint bake.") Because the paint bake generally occurs after natural aging and after the product is formed, high strength after the paint bake may be important. In one embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 240 MPa after 30 day NA+ paint bake. In another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 245 MPa after 30 day NA+ paint bake. In yet another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 250 MPa after 30 day NA+ paint bake. In another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 255 MPa with a 30 day NA+ paint bake. In yet another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 260 MPa with a 30 day NA+ paint bake. In another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 265 MPa with a 30 day NA+ paint bake. In yet another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 270 MPa with a 30 day NA+ paint bake.

[0029] As shown above, the new aluminum alloy sheet product may achieve a TYS-LT of at least 230 MPa when naturally aged for 90 days and then paint baked at 180°C for 20 minutes. (Herein, the phrase "when naturally aged for 90 days and then paint baked at 180°C for 20 minutes" is abbreviated to "90 day NA+ paint bake.") This may be important for low strength degradation after paint bake (e.g., to ensure the product retains high strength). In one embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 235 MPa when naturally aged for 90 days and then paint baked at 180°C for 20 minutes. In yet another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 240 MPa when naturally aged for 90 days and then paint baked at 180°C for 20 minutes. In yet another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 245 MPa when naturally aged for 90 days and then paint baked at 180°C for 20 minutes. In another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 250 MPa at 90 day NA+ paint bake.

[0030] As shown above, the new aluminum alloy sheet product may achieve a TYS-LT of at least 350 MPa when naturally aged for 30 days and then artificially aged at 180°C for 8 hours. (The phrase "when naturally aged for 30 days and then artificially aged at 180°C for 8 hours" is abbreviated herein to "30 days NA+AA.") In some embodiments, it may be useful to artificially age a product (e.g., a product that has been naturally aged and / or a product that has been paint baked) to increase its strength, and it may be important to achieve high strength. In one embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 355 MPa when NA+AA for 30 days. In another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 360 MPa when NA+AA for 30 days. In yet another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 365 MPa when NA+AA for 30 days. In another embodiment, the new aluminum alloy sheet product may achieve a TYS-LT of at least 370 MPa, 30 days NA+AA.

[0031] The T6 temper by artificial aging can be heating for any suitable period and at any suitable temperature. In one embodiment, the T6 temper is heating at 180°C for 8 hours or substantially similar aging conditions as shown above. As will be understood by those skilled in the art, the aging temperature and / or time can be adjusted based on well-known aging principles and / or formulas. Thus, those skilled in the art can increase the aging temperature while decreasing the aging time, or vice versa, or slightly change only one of these parameters and still achieve the same result as "aging at 180°C for 8 hours". Since there are many artificial aging techniques that would achieve the same result as "aging at 180°C for 8 hours", not all such alternative aging techniques are listed here. The use of the phrase "or substantially equivalent artificial aging temperature and duration" or the phrase "or substantially equivalent technique" is used to capture all such alternative aging techniques. As can be appreciated, these alternative artificial aging steps can occur in one or more steps and at one or more temperatures.

[0032] The new aluminum alloy sheet may also realize other important properties such as ductility and corrosion resistance. In one embodiment, the new aluminum alloy sheet product may realize at least 15% elongation (4D) in the T43 temper when tested according to ASTM E8 and B557. In another embodiment, the new aluminum alloy sheet product realizes at least 18% elongation in the T43 temper. In yet another embodiment, the new aluminum alloy sheet product realizes at least 20% elongation in the T43 temper. In another embodiment, the new aluminum alloy sheet product realizes at least 22% elongation in the T43 temper. In another embodiment, the new aluminum alloy sheet product realizes at least 24% elongation in the T43 temper. In yet another embodiment, the new aluminum alloy sheet product realizes at least 26% elongation in the T43 temper. In another embodiment, the new aluminum alloy sheet product realizes at least 28% elongation in the T43 temper.

[0033] In one embodiment, the new aluminum alloy sheet product may realize an elongation (4D) of at least 10% in the paint bake condition (e.g., T43+ paint bake) when tested according to ASTM E8 and B557. In another embodiment, the new aluminum alloy sheet product realizes an elongation of at least 12% in the paint bake condition. In yet another embodiment, the new aluminum alloy sheet product realizes an elongation of at least 14% in the paint bake condition. In another embodiment, the new aluminum alloy sheet product realizes an elongation of at least 16% in the paint bake condition. In yet another embodiment, the new aluminum alloy sheet product realizes an elongation of at least 18% in the paint bake condition. In another embodiment, the new aluminum alloy sheet product realizes an elongation of at least 20% in the paint bake condition.

[0034] In one embodiment, the new aluminum alloy sheet product may realize at least 10% elongation (4D) in the T6 temper when tested according to ASTM E8 and B557. In another embodiment, the new aluminum alloy sheet product realizes at least 11% elongation in the T6 temper. In yet another embodiment, the new aluminum alloy sheet product realizes at least 12% elongation in the T6 temper. In another embodiment, the new aluminum alloy sheet product realizes at least 13% elongation in the T6 temper. In yet another embodiment, the new aluminum alloy sheet product realizes at least 14% elongation in the T6 temper. In another embodiment, the new aluminum alloy sheet product realizes at least 15% elongation in the T6 temper.

[0035] In one embodiment, the novel aluminum alloy sheet product is corrosion resistant. In one embodiment, the corrosion resistance is at least intergranular corrosion resistance. In another embodiment, the corrosion resistance is at least filiform corrosion resistance. In another embodiment, the corrosion resistance is both intergranular corrosion resistance and filiform corrosion resistance. The intergranular corrosion resistance shall be measured according to ASTM G110 (5 test pieces). The filiform corrosion resistance is measured according to ASTM G85-2, and after exposing the sample for 3 weeks, it determines the resistance to the longest filiform corrosion perpendicular to each of three separate scribes.

[0036] In relation to the intergranular corrosion resistance, in one embodiment, the novel aluminum alloy sheet product achieves a maximum corrosion depth of 225 micrometers or less and an average corrosion depth of 150 micrometers or less.

[0037] In relation to the filiform corrosion resistance, in one embodiment, the novel aluminum alloy sheet product achieves a maximum corrosion track length of 0.35 inches or less, but is tested with at least 8 corrosion tracks. In another embodiment, the novel aluminum alloy sheet product achieves a maximum corrosion track length of 0.30 inches or less, but is tested with at least 8 corrosion tracks.

[0038] With the unique composition disclosed herein and appropriate processing, the novel aluminum alloy product can be crack-free after formation (for example, when pressed / formed into automotive components such as automotive panels). In one embodiment, the novel aluminum alloy product is crack-free after formation (for example, when pressed / formed into automotive panels / components), strong (after paint baking treatment and / or T6 sorting treatment, and as defined above), and corrosion resistant.

[0039] <iv. Product Applications> The novel aluminum alloy described in this specification can be used in various applications such as automotive, railway, aerospace, or consumer electronics applications. For example, the novel aluminum alloy can be formed into automotive parts. Non-limiting examples of automotive parts include the vehicle body and automotive panels. Non-limiting examples of automotive panels include, inter alia, outer panels and inner panels for use in automotive doors, automotive hoods, or automotive trunks (deck lids). An example of a vehicle body product can have structural components, which may be used when welding together the sheet metal components of the vehicle body (e.g., body-in-white). The novel aluminum alloy can also be used in other transportation applications such as light trucks or heavy trucks. Consumer electronics product applications include laptop computer cases and battery cases among other stamped and formed products.

[0040] <v.Representative, non-limiting items> The following are some non-limiting representative items that define one or more inventions. These items are non-limiting examples and are not intended to, nor do they, limit the inventions disclosed in this specification to the described matters. In fact, one or more inventions can be defined using any of the subject matter described in this specification.

[0041] Item 1. An aluminum alloy sheet product, 0.70 to 1.4 wt% Si, 0.70 to 1.3 wt% Mg, where (wt% of Mg) / (wt% of Si) is 1.4:1 or less, 0.70 to 3.0 wt% Zn, 0.55 to 1.3 wt% Cu, where the total amount of Si + Mg + Zn + Cu is 4.25 wt% or less, 0.01 to 0.30 wt% Fe, up to 0.70 wt% Mn, up to 0.15 wt% Cr, Zr up to 0.20 wt.%; V up to 0.20 wt.%; and up to 0.25 wt.% Ti, The balance is aluminum, optional unavoidable elements and impurities. The aluminum alloy sheet product has a thickness of 1.0 to 4.0 mm; The aluminium sheet product has the following properties: (i) TYS-LT of 155 MPa or less after 7 days of natural aging ("TYS-7NA"); (ii) TYS-LT of 175 MPa or less after 90 days of natural aging ("TYS-90NA"); (iii) (TYS-90NA) minus (TYS-7NA) is 20 MPa or less. (iv) After natural aging for 30 days and then paint baking at 180°C for 20 minutes, TYS-LT has a strength of at least 235 MPa; (v) After natural aging for 90 days and then paint baking treatment at 180°C for 20 minutes, TYS-LT has a strength of at least 230 MPa; (vi) an aluminum alloy sheet product having a TYS-LT of at least 350 MPa when naturally aged for 30 days and then artificially aged at 180°C for 8 hours;

[0042] Item 2. The aluminum alloy sheet product of item 1, wherein the aluminum alloy comprises at least 0.75 wt.% Si, or at least 0.80 wt.% Si, or at least 0.85 wt.% Si.

[0043] Item 3. The aluminum alloy sheet product according to items 1 to 2, wherein the aluminum alloy contains 1.35% by weight or less of Si, or 1.30% by weight or less of Si, or 1.25% by weight or less of Si, or 1.20% by weight or less of Si, or 1.15% by weight or less of Si, or 1.10% by weight or less of Si, or 1.05% by weight or less of Si.

[0044] Item 4. The aluminum alloy sheet product according to any one of items 1 to 3, wherein the aluminum alloy contains at least 0.75 wt.% Mg, or at least 0.80 wt.% Mg.

[0045] Item 5. The aluminum alloy sheet product according to any one of items 1 to 4, wherein the aluminum alloy contains 1.25 wt.% or less of Mg, or 1.20 wt.% or less of Mg, or 1.15 wt.% or less of Mg, or 1.10 wt.% or less of Mg, or 1.05 wt.% or less of Mg.

[0046] Item 6. The aluminum alloy sheet product according to any one of Items 1 to 5, wherein (wt% of Mg) / (wt% of Si) is 1.3:1 or less, or 1.2:1 or less.

[0047] Item 7. The aluminum alloy sheet product according to any one of items 1 to 6, wherein (wt% Mg) / (wt% Si) is at least 0.7:1, or at least 0.8:1, or at least 0.9:1.

[0048] Item 8. The aluminum alloy sheet product according to any one of items 1 to 7, wherein the aluminum alloy contains at least 0.75 wt.% Zn, or at least 0.85 wt.% Zn, or at least 0.95 wt.% Zn, or at least 1.0 wt.% Zn, or at least 1.05 wt.% Zn.

[0049] Item 9. The aluminum alloy sheet product according to any one of items 1 to 8, wherein the aluminum alloy contains 2.8% by weight or less of Zn, or 2.6% by weight or less of Zn, or 2.4% by weight or less of Zn, or 2.2% by weight or less of Zn, or 2.0% by weight or less of Zn, or 1.8% by weight or less of Zn.

[0050] Item 10. The aluminum alloy sheet product according to any one of items 1 to 9, wherein the aluminum alloy contains at least 0.60 wt.% Cu, or at least 0.65 wt.% Cu, or at least 0.70 wt.% Cu.

[0051] Item 11. The aluminum alloy sheet product according to any one of items 1 to 10, wherein the aluminum alloy contains 1.25 wt.% Cu or less, or 1.20 wt.% Cu or less, or 1.15 wt.% Cu or less, or 1.10 wt.% Cu or less, or 1.05 wt.% Cu or less.

[0052] Item 12. The aluminum alloy sheet product according to any one of items 1 to 11, wherein the aluminum alloy contains at least 0.05 wt.% Fe, or at least 0.10 wt.% Fe, or at least 0.12 wt.% Fe.

[0053] Item 13. The aluminum alloy sheet product according to any one of items 1 to 12, wherein the aluminum alloy contains 0.25% by weight or less of Fe, or 0.22% by weight or less of Fe, or 0.19% by weight or less of Fe, or 0.16% by weight or less of Fe.

[0054] Item 14. The aluminum alloy sheet product according to any one of items 1 to 13, wherein the aluminum alloy contains at least 0.05 wt.% Mn, or at least 0.10 wt.% Mn, or at least 0.15 wt.% Mn.

[0055] Item 15. The aluminum alloy sheet product according to any one of items 1 to 14, wherein the aluminum alloy contains 0.60 wt.% or less Mn, or 0.50 wt.% or less Mn, or 0.45 wt.% or less Mn, or 0.40 wt.% or less Mn.

[0056] Item 16. The aluminum alloy sheet product according to any one of items 1 to 15, wherein the aluminum alloy contains 0.12 wt% or less of Cr, or 0.10 wt% or less of Cr, or 0.08 wt% or less of Cr, or 0.06 wt% or less of Cr, or 0.04 wt% or less of Cr, or 0.03 wt% or less of Cr, or 0.02 wt% or less of Cr, or 0.01 wt% or less of Cr.

[0057] Item 17. The aluminum alloy sheet product according to any one of items 1 to 16, wherein the aluminum alloy contains 0.15 wt.% Zr or less, or 0.10 wt.% Zr or less, or 0.08 wt.% Zr or less, or 0.05 wt.% Zr or less, or 0.03 wt.% Zr or less.

[0058] Item 18. The aluminum alloy sheet product according to any one of items 1 to 17, wherein the aluminum alloy contains at least 0.01 wt.% Zr.

[0059] Item 19. The aluminum alloy sheet product according to any one of items 1 to 18, wherein the aluminum alloy contains 0.15 wt.% or less of V, or 0.10 wt.% or less of V, or 0.08 wt.% or less of V, or 0.05 wt.% or less of V, or 0.03 wt.% or less of V.

[0060] Item 20. The aluminum alloy sheet product according to any one of items 1 to 19, wherein the aluminum alloy contains at least 0.01 wt.% V.

[0061] Item 21. The aluminum alloy sheet product according to any one of items 1 to 20, wherein the aluminum alloy contains 0.12 wt.% or less of Ti, or 0.10 wt.% or less of Ti.

[0062] Item 22. The aluminum alloy sheet product according to any one of items 1 to 21, wherein the aluminum alloy contains at least 0.01 wt.% Ti, or at least 0.02 wt.% Ti, or at least 0.05 wt.% Ti.

[0063] Item 23. An automotive seat product made from the aluminum alloy sheet product according to any one of items 1 to 22.

[0064] Item 24. The automobile seat product according to item 23, wherein the automobile seat product realizes at least two of the properties (i) to (vi).

[0065] Item 25. The automobile seat product according to item 23, wherein the automobile seat product realizes at least three of the properties (i) to (vi).

[0066] Item 26. The automobile seat product according to item 23, wherein the automobile seat product realizes at least four of the properties (i) to (vi).

[0067] Item 27. The automobile seat product according to item 23, wherein the automobile seat product realizes at least five of the properties (i) to (vi).

[0068] Item 28. The automobile seat product according to item 23, wherein the automobile seat product realizes all of the properties (i) to (vi).

[0069] Item 29. The sheet product for automobiles according to any one of items 23 to 28, wherein the sheet product realizes the property (i), and wherein the property (i) is 155 MPa or less, or 150 MPa or less, or 145 MPa or less.

[0070] Item 30. The sheet product according to any one of items 23 to 29, wherein the sheet product achieves the property (ii), and the property (ii) is 175 MPa or less, or 170 MPa or less, or 165 MPa or less, or 160 MPa or less, or 155 MPa or less.

[0071] Item 31. The sheet product according to any one of items 23 to 30, wherein the sheet product achieves the property (iii), and the property (iii) is 20 MPa or less, or 18 MPa or less, or 15 MPa or less, or 12 MPa or less, or 10 MPa or less, or 8 MPa or less.

[0072] Item 32. The sheet product according to any one of items 23 to 31, wherein the sheet product achieves the property (iv), and the property (iv) is at least 235 MPa, or at least 240 MPa, or at least 250 MPa, or at least 255 MPa, or at least 260 MPa, or at least 265 MPa, or at least 270 MPa.

[0073] Item 33. The sheet product according to any one of items 23 to 32, wherein the sheet product achieves the property (v), and the property (v) is at least 230 MPa, or at least 235 MPa, or at least 240 MPa, or at least 245 MPa, or at least 250 MPa.

[0074] Item 34. The sheet product according to any one of items 23 to 33, wherein the sheet product achieves the property (vi), and wherein the property (vi) is at least 350 MPa, or at least 355 MPa, or at least 360 MPa, or at least 365 MPa, or at least 370 MPa.

[0075] Item 35. The sheet product according to any one of items 23 to 34, wherein the sheet product realizes at least 15% elongation, or at least 18% elongation, or at least 20% elongation, or at least 22% elongation, or at least 24% elongation, or at least 26% elongation, or at least 28% elongation in temper T43.

[0076] Item 36. The sheet product according to any one of items 23 to 35, wherein the sheet product realizes at least 10% elongation, or at least 12% elongation, or at least 14% elongation, or at least 16% elongation, or at least 18% elongation, or at least 20% elongation after paint baking treatment at 180 ° C. for 20 minutes.

[0077] Item 37. The automotive seat product according to any one of items 23 to 36, wherein the sheet product achieves at least 10% elongation, or at least 11% elongation, or at least 12% elongation, or at least 13% elongation, or at least 14% elongation, or at least 15% elongation after artificial aging at 180 ° C. for 8 hours.

[0078] Item 38. The automotive seat product according to any one of items 23 to 37, wherein the seat product is resistant to intergranular corrosion.

[0079] Item 39. The seat product according to any one of Items 23 to 38, wherein the seat product shows resistance to filiform corrosion.

[0080] Item 40. The seat product according to any one of Items 23 to 37, wherein the seat product has no cracks.

[0081] <vi. Various matters> These aspects and other aspects, advantages, and novel features of this new technology will become apparent to those skilled in the art in part in the following description and consideration of the drawings that follow, or can be learned by implementing one or more embodiments of the technology provided by this disclosure.

[0082] Among the advantages and improvements disclosed, other objects and advantages of the present invention will become apparent from the following description together with the accompanying drawings. Although detailed embodiments of the present invention are disclosed herein, it should be understood that the disclosed embodiments are merely illustrative of the present invention which can be embodied in various forms. Furthermore, each example set forth in connection with various embodiments of the present invention is intended to be illustrative and not limiting.

[0083] Throughout the specification and the claims, the following words take the meanings specifically related to this specification unless otherwise clearly indicated in the context. The phrases "in one embodiment" and "in some embodiments" used in this specification do not necessarily refer to the same embodiment, but may do so. Furthermore, the phrases "in another embodiment" and "in some other embodiments" used in this specification do not necessarily refer to different embodiments, but may do so. Therefore, various embodiments of the present invention may be easily combined without departing from the scope or spirit of the present invention.

[0084] Additionally, as used herein, the term "or" is an inclusive "or" modifier and is equivalent to the term "and / or" unless the context clearly dictates otherwise. The term "based on" is not exclusive and may be based on additional unrecited elements unless the context clearly dictates otherwise. Additionally, throughout this specification, "a," "an," and "the" include the plural meanings unless the context clearly dictates otherwise. "In" includes the meanings "in" and "on" unless the context clearly dictates otherwise.

[0085] While several embodiments of the present invention have been described, it should be understood that these embodiments are merely illustrative and not limiting, and that many variations may become apparent to those skilled in the art. Moreover, unless the context clearly dictates otherwise, the various steps may be performed in any desired order, and any applicable steps may be added and / or removed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES

[0086] Thirty alloys were cast into 6 inch by 18 inch ingots. The compositions of these ingots are provided in Table 1 below. [Table 1] *The balance of each alloy was 0.02-0.03 wt% Ti, Aluminum, unavoidable elements and impurities, with each alloy containing no more than 0.03 wt% of any one impurity, and so each alloy contained no more than 0.10 wt% of all impurities in total. **Alloy 29 is an AA6055 type alloy according to U.S. Patent No. 6,537,392. The Aluminum Association composition limits for AA6055 alloy are as follows: 0.6-1.2 wt% Si, 0.30(max) wt% Fe, 0.50-1.0 wt% Cu, 0.10(max) wt% Mn, 0.7-1.1 wt% Mg, 0.20-0.30 wt% Cr, 0.55-0.9 wt% Zn, 0.10(max) wt% Ti, 0.05(max) wt% impurities, 0.15(max) wt% total other impurities, balance Aluminum. (“International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys,” January 2015, page 10, The Aluminum Association, 1525 Wilson Boulevard, Arlington, VA 22209.) Alloys 18, 21-22 and 27 are invention alloys. Alloys 1-17, 19-20, 23-26 and 28-30 are non-invention alloys and are highlighted in grey.

[0087] The ingots were homogenized after casting and then rolled into final gauge sheet products. The final gauge sheet products had a thickness of 2 mm. The final gauge sheet products were then solution heat treated, quenched to room temperature, and then reheated to a pre-aging temperature of 82°C (179.6°F), and then subjected to a simulated coil cool by holding in a furnace programmed to cool at a predetermined cooling rate (following Newtonian cooling) to give the alloys temper T43. The natural aging response of the alloys was then evaluated by measuring the mechanical properties of each alloy at 7 days and 90 days of natural aging (measured from the time the alloy was quenched after the solution heat treatment). The paint bake response of the T43 temper alloys was also tested by heating at 180°C for 20 minutes. The artificial aging response of the alloys was also tested by aging the T43 temper alloys at 180°C for 8 hours (T6 type temper). The experimental results are provided in Table 2 below, where all values ​​shown are TYS-LT (transverse tensile yield strength) and are in MPa, NA = natural aging, PB = paint baked as above, and T6 = artificial aging as above. [Table 2] *Values ​​for Alloys 2 to 4 are after 60 days of natural aging treatment.

[0088] <Natural Aging Properties>: As shown, non-invention alloys 1-8, 10, 16, 26, and 28 do not meet the TYS-LT parameters of 155 MPa or less for 7 days of natural aging and / or 175 MPa or less for 90 days of natural aging. Furthermore, the strength of non-invention alloys 8, 13, 17, 20, and 30 increased excessively (20 MPa or more) from 7 days to 90 days of natural aging. Achieving strengths of 155 MPa or less for 7 days of natural aging, 175 MPa or less for 90 days of natural aging, and a strength increase of 20 MPa or less from 7 days to 90 days of natural aging is important for formability. NOTE: Natural aging test data for the invention alloy 22 is not included because B557 test specimens for this alloy were inadequate for other unrelated reasons. However, based on additional testing, it is believed that alloy 22 will meet the requirements of TYS-LT ≤ 155 after 7 days of natural aging, TYS-LT ≤ 175 after 90 days of natural aging, and TYS-LT increase ≤ 20 MPa from 7 days to 90 days of natural aging.

[0089] <Paint bakeability>: As shown, non-invention alloys 9, 11, 13-15, 17, 20, 23 and 25 achieved insufficient strength after paint baking, with TYS-LT less than 235 MPa 30 days after paint baking and / or TYS-LT less than 230 MPa 90 days after paint baking. The low strength after paint baking and loss of strength over time after paint baking are unacceptable for most automotive applications.

[0090] <Artificial aging properties>: As shown, non-inventive alloys 9-10, 13-15, 20, 23, 25, and 30 all achieved insufficient artificial aging strength with TYS-LT less than 350 MPa after artificial aging. The low artificial aging strength may make the alloys unsuitable for some automotive applications.

[0091] Apart from the mechanical properties, the corrosion resistance of some alloys was also tested and the results are provided in Tables 3-4 below. [Table 3] [Table 4]

[0092] As shown, the intergranular corrosion resistance of these alloys is generally acceptable. However, the filiform corrosion of alloys 6-7, 10, 14, and 24 is excessively high, exceeding 0.30 inches, based on maximum length. Alloy 12 is expected to behave similarly to alloys 10 and 14 with respect to filiform corrosion, and therefore is considered a non-invention alloy. Alloy 19 is expected to behave similarly to alloy 24 with respect to filiform corrosion, and therefore is considered a non-invention alloy.

[0093] These results suggest that alloying elements need to be used in specific combinations to achieve a combination of properties that may be important for aluminum alloy sheet products. Specifically, alloys with excess solutes (e.g., alloys 1-8, 25-26, 28) may achieve unacceptable strength and / or corrosion resistance. That is, the total of Si+Mg+Zn+Cu is limited to 4.25 wt.% or less. Specific amounts of silicon and magnesium are also important. Too little silicon (e.g., alloys 15 and 23) results in poor properties. Furthermore, the Mg:Si ratio needs to be 1.4 or less, as shown by alloys 15 and 25, where a high Mg:Si ratio was at least partially responsible for the poor strength. Copper and zinc both need to be used in large amounts to achieve good strength and corrosion resistance. This is shown by contrasting inventive alloys 18, 21-22, and 27 with various non-inventive alloys. Finally, chromium should be avoided as it can negatively impact the potential properties (according to Alloy 30) and also affect the recyclability of the alloy.

[0094] While various embodiments of the present disclosure have been described in detail, it is apparent that variations and modifications to those embodiments will occur to those skilled in the art, but it should be expressly understood that such variations and modifications are within the spirit and scope of the present disclosure.

Claims

1. 1. An aluminium alloy sheet product comprising: 0.85 to 1.05 wt.% Si; 0.70 to 1.3 wt. % Mg; wherein (wt. % Mg) / (wt. % Si) is not greater than 1.4 / 1; 0.70 to 3.0 wt. % Zn; 0.55 to 1.3 wt.% Cu; wherein the total amount of Si+Mg+Zn+Cu is 4.25% by weight or less; 0.01 to 0.30 wt. % Fe; Mn up to 0.70 wt.%; % Cr max. % Zr; Maximum 0.20 wt.% V; and max 0.25 wt.% Ti, The balance is aluminum, optional unavoidable elements and impurities. The aluminum alloy sheet product has a thickness of 1.0 to 4.0 mm.

2. 2. The aluminum alloy sheet product of claim 1, wherein the aluminum alloy comprises at least 0.75 wt.% Mg.

3. 3. The aluminum alloy sheet product of claim 2, wherein the aluminum alloy comprises up to 1.25 wt.% Mg.

4. 2. The aluminum alloy sheet product of claim 1, wherein (wt %) Mg / (wt %) Si is not greater than 1.3 / 1.

5. 5. An aluminum alloy sheet product according to claim 4, wherein (wt % Mg) / (wt % Si) is at least 0.7 / 1.

6. The aluminum alloy sheet product of claim 1 , wherein the aluminum alloy comprises at least 0.75 wt.% Zn.

7. 7. The aluminum alloy sheet product of claim 6, wherein the aluminum alloy comprises up to 2.8 wt.% Zn.

8. The aluminum alloy sheet product of claim 1 , wherein the aluminum alloy comprises at least 0.60 wt.% Cu.

9. The aluminum alloy sheet product of claim 8, wherein the aluminum alloy comprises up to 1.25 wt.% Cu.

10. 10. An automotive seat product made from the aluminum alloy sheet product according to any one of claims 1 to 9.

11. 1. An aluminium alloy sheet product comprising: 0.85 to 1.05 wt.% Si; 0.80 to 1.10 wt. % Mg; 0.70 to 1.8 wt. % Zn; 0.70 to 1.05 wt.% Cu; wherein the total amount of Si+Mg+Zn+Cu is 4.25% by weight or less; 0.01 to 0.30 wt. % Fe; Mn up to 0.50 wt.%; % Cr max. % Zr; Maximum 0.20 wt.% V; and max 0.25 wt.% Ti, The balance is aluminum, optional unavoidable elements and impurities. The aluminum alloy sheet product has a thickness of 1.0 to 4.0 mm.

Citation Information

Patent Citations

  • Aluminum-magnesium-silicon alloy sheet excellent in formability and its production

    JP1997031616A

  • Production of aluminum alloy sheet excellent in forming workability and hardenability in coating / baking

    JP1997143645A

  • Production of aluminum alloy for baking finish, excellent in chemical conversion treating property and corrosion resistance after coating, and baking-finished aluminum alloy material

    JP1998176233A

  • Aluminium alloy conductor and manufacturing method for same

    WO2012011513A1